Influence from the free volume on the photoinduced birefringence in azocompound-containing polymers - Dall'Agnol, F. F.; Oliveira, O. N.; Giacometti, J. A. (Amer Chemical Soc, 2006)
The photoinduced birefringence is analyzed in a guest-host azobenzene-containing polymer in the temperature range from 20 to 330 K. An anomalous behavior arises in the low-temperature range, suggesting strong influence from the free volume for the chromophores in the polymer. This influence is so strong that quenched samples have a photoinduced signal ca. 5 times greater than the annealed ones at room temperature. An extended free volume model is presented based on two assumptions about thermal fluctuations in the cavities and their size distribution. This model, which is an extension of the model by Mita et al., can explain the main features of the photoinduced birefringence as a function of time, temperature, and initial free volume state. To account for the influence of free volume on the photoorientation, the detailed reorientation model by Sekkat's was used. We show that Sekkat's model leads to an exponential behavior at small orientation regimes, which simplifies the mathematical treatment and allows the mean free volume to be obtained from the data fitting.